An analysis of effects of heterozygosity in dairy cattle for bovine tuberculosis resistance. (24th January 2018) - Tsairidou, S.; Allen, A. R.; Pong‐Wong, R.; McBride, S. H.; Wright, D. M.; Matika, O.; Pooley, C. M.; McDowell, S. W. J.; Glass, E. J.; Skuce, R. A.; Bishop, S. C.; Woolliams, J. A.
Summary: Genetic selection of cattle more resistant to bovine tuberculosis (bTB) may offer a complementary control strategy. Hypothesising underlying non‐additive genetic variation, we present an approach using genome‐wide high density markers to identify genomic loci with dominance effects on bTB resistance and to test previously published regions with heterozygote advantage in bTB. Our data comprised 1151 Holstein–Friesian cows from Northern Ireland, confirmed bTB cases and controls, genotyped with the 700K Illumina BeadChip. Genome‐wide markers were tested for associations between heterozygosity and bTB status using marker‐based relationships. Results were tested for robustness against genetic structure, and the genotypic frequencies of a significant locus were tested for departures from Hardy‐Weinberg equilibrium. Genomic regions identified in our study and in previous publications were tested for dominance effects. Genotypic effects were estimated through ASReml mixed models. A SNP (rs43032684) on chromosome 6 was significant at the chromosome‐wide level, explaining 1.7% of the phenotypic variance. In the controls, there were fewer heterozygotes for rs43032684 ( P < 0.01) with the genotypic values suggesting that heterozygosity confers a heterozygote disadvantage. The region surrounding rs43032684 had a significant dominance effect ( P < 0.01). SNP rs43032684 resides within a pseudogene with a parental gene involved in macrophage response to infection and within a copy‐number‐variation region previously associated with nematode resistance. No dominance effect was found for the region on chromosome 11, as indicated by a previous candidate region bTB study. These findings require further validation with large‐scale data.